Conocimiento alimentario de padres, hábitos alimentarios, y estado nutricional en preescolares de la institución educativa N°690 Santa Mónica, 2024 - Marin Aguilar, Liseth Ana Paula (2025)
The aim of this study was to determine the relationship between parental dietary knowledge, eating habits and nutritional status in preschoolers of the Educational Institution N°690 Santa Monica, in the year 2024. The research had a quantitative approach, non-experimental, descriptive-correlational and cross-sectional design. A total of 251 parents and 251 preschool children were evaluated by means of food knowledge and food consumption frequency questionnaires, together with anthropometric and hemoglobin measurements. The results showed that 99 % of the parents had high dietary knowledge; however, no significant correlation was found with the nutritional status of the preschoolers. There was a high prevalence of unhealthy eating habits in the children (75 % in boys and 84 % in girls), as well as cases of malnutrition, overweight and anemia. Malnutrition was found in 18.4 % of boys and 14.9 % of girls, while overweight affected 31.1 % of girls and 2.9 % of boys. It is concluded that, although parents have a high level of knowledge about nutrition, this does not translate into better feeding practices or adequate child nutritional status. It is recommended that more practical and accessible educational strategies be implemented to improve children's eating habits and nutrition.